Papa's mechanical fish - Fleming, Candace (Margaret Ferguson Books, Farrar Straus Giroux, 2013)
In the summer of 1851, with encouragement and ideas provided by his family, an inventor builds a working submarine and takes his family for a ride. Includes notes about Lodner Phillips, the real inventor on whom the story is based.